RESPONSES OF PLASMA TRANSAMINASE ACTIVITY IN CYPRINUS CARPIO VAR. COMMUNIS TO MERCURY TOXICITY - Sampath, Hannah; Ramesh, M.; Manavalaramanujam, Manavalaramanujam (Journal of Indian Fisheries Association, 2015)
The present study reports the behavioural and enzymological responses in a freshwater teleost fish, Cyprinus carpio var. communis, exposed to acute and sublethal toxicities of mercuric chloride. During acute treatement, significant behavioural changes like erratic swimming, excess mucus secretion, increased opercular movements, etc. were noticed. During acute and sublethal treatments, both aspartate amino transferase and alanine amino transferase activity increased throughout the study period. Comparing the treatments, the changes in enzyme activities were found high in acute treatement and all the values were significant at 5% level. The above findings can be used as non-specific biomarkers of environmental pollutants. Keywords: Mercuric chloride, AST, ALT, Cyprinus carpio